IGF-I in cord blood is predictive of final height in monozygotic twins with intra-twin birth weight differences - Kasner, Charlotte; Schulte, Sandra; Schreiner, Felix; Fimmers, Rolf; Stoffel-Wagner, Birgit; Bartmann, Peter; Wölfle, Joachim; Gohlke, Bettina (Clinical Endocrinology, 2020)
Objective: Adverse prenatal conditions can exert a long-lasting impact on growth up to final height (FH). Due to different prenatal nutrient availability, monozygotic twin pairs with discordant birth weight (bw) provide an excellent model to examine the impact of genes and environment and to analyse the predictive value of bw, birth length (bl) and cord blood (cb) concentration of IGF-I on FH. Patients and Methods: Twenty eight monozygotic twin pairs with intra-twin bw-/bl-differences were studied at birth and longitudinally until FH. Intra-twin bw difference >1 SDS was defined “discordant” (n = 10 pairs). IGF-I was analysed in cord blood in all twins. Intra-twin differences (∆) in bw, bl and cord blood IGF-I were correlated with ∆FH. Results: Throughout growth and up until FH intra-twin length/height differences remained for all but two (26/28) twins and for all (10/10) discordant twins. In the discordant group, a highly significant intra-twin difference for FH-SDS was found with a mean intra-twin Δheight- SDS of 1.23 (range, 0.29-2.34). This corresponds to a mean Δintra-twin difference at FH of 7.9 cm (3.1 inch; range, 2-15 cm [0.79-5.9 inch]). Correlation coefficients were calculated to identify factors predicting FH: ∆bw (r =.678; P =.0005), ∆bl (r =.333; P =.0002) and ∆IGF-I in cb (r =.418; P =.0023). Interaction terms showed that IGF-I is an additional factor to the auxological data, leading to an improvement of the ∆FH modelling. Conclusion: Prenatal environment leading to bw-/bl- and cbIGF-I differences in monozygotic twins had a long-lasting impact on growth until FH. Both, anthropometric data at birth and cbIGF-I are predictive of FH.
CRIS-Team Scopus Importer:2020-06-19
Keywords: birth length; birth weight; final height; foetal programming; growth; IGF-I